The effect of a methyl group on structure and function: Serine vs. threonine glycosylation and phosphorylation - Barchi, Joseph J.; Strain, Caitlin N. (Frontiers in Molecular Biosciences, 2023)
A variety of glycan structures cover the surface of all cells and are involved in myriad biological processes, including but not limited to, cell adhesion and communication, protein quality control, signal transduction and metabolism while also being intimately involved in innate and adaptive immune functions. Immune surveillance and responses to foreign carbohydrate antigens, such as capsular polysaccharides on bacteria and surface protein glycosylation of viruses are the basis of microbial clearance, and most antimicrobial vaccines target these structures. In addition, aberrant glycans on tumors called Tumor-Associated Carbohydrate Antigens (TACAs) elicit immune responses to cancer, and TACAs have been used in the design of many antitumor vaccine constructs. A majority of mammalian TACAs are derived from what are referred to as mucin-type O-linked glycans on cell-surface proteins and are linked to the protein backbone through the hydroxyl group of either serine or threonine residues. A small group of structural studies that have compared mono- and oligosaccharides attached to each of these residues have shown that there are distinct differences in conformational preferences assumed by glycans attached to either “unmethylated” serine or -methylated threonine. This suggests that the linkage point of antigenic glycans will affect their presentation to the immune system as well as to various carbohydrate binding molecule (e.g., lectins). This short review, followed by our hypothesis will examine this possibility and extend the concept to the presentation of glycans on surfaces and in assay systems where recognition of glycans by proteins and other binding partners can be defined by different attachment points that allow for a range of conformational presentations.